Analisis Stakeholder Dalam Pengembangan Kualitas Sumber Daya Manusia Dinas Pendidikan Kabupaten Sampang : Studi Pada Bidang Pembinaan Guru Tenaga Kependidikan, Pengembangan Bahasa dan Sastra - Aldian Cholik; Adi Soesiantoro; Anggraeny Puspaningtyas (Journal of Research and Development on Public Policy, 2024)
In 2023, Sampang Regency will still be called the district with the lowest HDI of the 39 cities/districts in East Java. The lack of stakeholder roles in contributing to the success of increasing human resources in the field of Educational Teachers (GTK) will affect the effectiveness of the organization in achieving its goals. Moreover, it will also have an impact on the quality of the organization, because the role of stakeholders and the quality of human resources play a very important role in the success of an organization. The aim of this research is to analyze stakeholders and the role of stakeholders in developing the quality of human resources. The research uses qualitative research with a descriptive approach. Based on the research results, the application of stakeholder analysis in developing the quality of human resources in the Sampang District Education Office is quite good and plays appropriate tasks such as the involvement of primary stakeholders such as GTK staff, school principals and teachers, key stakeholders are played by the Head of the Department, secondary stakeholders such as the Ministry of Education and Accreditation Body. Meanwhile, the role of various stakeholders in developing human resources in the Sampang Regency Education Service is considered very important, here are some of the roles of the stakeholders: Head of the Education Service as policy creator, Head of GTK Division as coordinator, Facilitators such as Secretary and Head of GTK Section, Implementors such as School Principals and Teachers, Accreditation Body and Ministry of Education as accelerators.